Finite Element Analysis on Brake Disc of an Educational All-Terrain-Vehicle - Hassan, Muhammad Zahir; Abdul Munir, Fudhail; Salim, Mohd Azli (Trans Tech Publications, Switzerland, 2015)
All-terrain vehicle is famously used for various purposes such as in civilian and military.The use of finite element analysis in a preliminary design stage has been demonstrated to be cost and time effective. In this paper, the finite element analysis of a brake disc for All-Terrain-Vehicle (ATV) is demonstrated. Eulerian-Lagrangian method was employed in this work where simple annular ring was used as the disc model. This study is limited to thermal and contact analysis between the disc and brake pad. The results in term of temperature and stresses distribution is obtained and presented. Moreover, the lateral displacement of the disc due to the friction contact is also shown. These results are then used to as a technical guideline in designing brake system for a fully customized ATV.